Wind Power-Future of Belarusian Power Industry - M. M. Oleshkevich; I. V. Makosko; V. M. Oleshkevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers peculiar features concerning introduction of wind power in Belarus. Expediency and necessity of its introduction irrespective of nuclear power station construction are shown in the paper. The paper contains recommendations for selection of installation parameters, their peculiar features in design and their location.